2004
DOI: 10.1381/0960892042387101
|View full text |Cite
|
Sign up to set email alerts
|

Routine Abdominal Drains After Laparoscopic Roux-en-Y Gastric Bypass: A Retrospective Review of 593 Patients

Abstract: The routine use of abdominal drains after LRYGBP appears to be beneficial. Drains allowed early diagnosis of complications and in most cases, the successful treatment of leaks. When bleeding is suspected or documented, appropriate volume replacement therapy is mandatory to maintain adequate hemodynamic parameters. Drain output may orient the surgeon to take preventive measures such as discontinuing anticoagulation and early fluid resuscitation. In this series, in most cases the bleeding spontaneously stopped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 12 publications
1
23
0
3
Order By: Relevance
“…Key words: UGI series -Drains -Anastomotic leak -Gastric bypass -Bariatric surgery The use of abdominal drains and upper GI (UGI) series are often cited as routine in the care of the perioperative management of the bariatric surgery patient [1].…”
Section: Introductionmentioning
confidence: 99%
“…Key words: UGI series -Drains -Anastomotic leak -Gastric bypass -Bariatric surgery The use of abdominal drains and upper GI (UGI) series are often cited as routine in the care of the perioperative management of the bariatric surgery patient [1].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leaks, although rare, are one of the most common major postoperative complications of bariatric operations [1]. Many surgeons have reported the rate of anastomotic leaks of less than 1% [7] while some reported higher rates [6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Chousleb, et al [1] in his study aimed to assess if the drain placement provides additional therapeutic advantages in the management of patients with leaks after gastric bypass bariatric surgery. He concluded that the use of drain may provide added safety in the postoperative care of these patients and help deal with its complications [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations